The Role of Information and Communication Technologies (ICT) in the Urban Adaptation and Socio-Academic Integration of Immigrant Students: The Case of Istanbul - Altundal, Meryem; Kurtarır, Erhan (Border Crossing, 2025)
This study examines the role of information and communication technologies (ICT) in the urban adaptation and socio-academic integration processes of immigrant students studying in Istanbul. Based on a literature-driven analysis, the research identifies the opportunities digital tools offer in areas such as language learning, social connection, and academic achievement. It highlights structural barriers including digital inequality, lack of multilingual content, and limited digital literacy. The study argues that ICT can be a strategic tool for integration when supported by inclusive content, digital literacy training, and participatory policies.